Symmetric impact of FDI on energy consumption: Evidence from Ghana. (15th May 2021) - Amoako, Samuel; Insaidoo, Michael
Abstract: Given Ghana's steadily increasing levels of foreign direct investment (FDI) over time, it is imperative to understand how FDI can assist to minimise the energy consumption level which will help the country stay on course to achieve target 7 of the Sustainable Development Goals (SDG) of achieving energy efficiency by 2030. Therefore, using annual time series data on Ghana, the present study examines the link between foreign direct investment and energy consumption for the 1981 to 2014 period. Overall, there exist cointegration between the variables in the long run when Johansen multivariate test was conducted. Results from the Fully Modified Ordinary Least Squares (FMOLS) and the Canonical Cointegration Regression (CCR) show that FDI and industry value-added positively correlates with energy consumption whilst financial development and energy price are inversely related to energy consumption. The results suggest that energy savings benefit from FDIs is yet to be realised in Ghana. Based on the results, we provide some important policy recommendations that focus on technological absorption, industrial structure optimization as well as Science, Technology, Engineering, and Mathematics (STEM) education and tax concessions. Highlights: Symmetrically, FDI levels does not automatically connote energy savings transfer. Strategic energy price adjustments can reduce energy consumption. Effective national energy consumption policies can help reduce consumption levels. Economic integration inversely relates with energy consumption.